The Effect of Self-Esteem on the Development of Narcissistic Behavior Among Students Engaged in Social Media - Hafni, Merri (Bulletin of Counseling and Psychotherapy, 2025)
The increasing prevalence of social media usage among university students has raised significant concerns about its psychological effects, particularly in relation to self-esteem and the development of narcissistic behavior. As students spend more time engaging with social media platforms, behaviors such as seeking validation through "likes" and comments or frequently uploading self-promoting content have become more common. This study aims to determine and analyze the effects of self-esteem on narcissistic behavior in students at Medan Area University. The research design used in this study is survey research. The research sample consisted of 265 students of Medan Area University consisting of various durations of smartphone use. Data collection was carried out through two questionnaires measuring self-esteem and narcissistic behavior. This study was analyzed using simple linear regression. The results of the study showed that self-esteem had a significant positive effect on narcissistic behavior, the greater the narcissistic tendency. Students with low self-esteem were less likely to exhibit narcissistic behavior such as frequently uploading photos of themselves and seeking attention through "likes" and comments.